The role of the Eu3+ ions in structure and photoluminescence properties of SrBi2Nb2O9 powders - Volanti, Diogo P. [UNESP]; Rosa, Ieda L. V.; Paris, Elaine C.; Paskocimas, Carlos A.; Pizani, Paulo S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2009)
This work rationalized for the first time the key role of Eu3+ ion in the doping process of SrBi2Nb2O9 (SBN) compound. This process allows LIS to understand the role of Eu3+ as lattice modifier as well as to obtain information on the crystalline structure surrounding. Therefore, the SBN and Eu3+ doped SBN (SBN:Eu) were synthesized using the polymeric precursor method (PPM). Scanning electron microscope (SEM) images reveal the strong influence of europium on the SBN microstructure. Thermogravimetry (TG) and differential thermal analysis (DTA) techniques were used to determine the weight loss and changes associated with phase transitions in SBN during thermal evolution. The behavior of the Eu3+ lattice modifier was followed in a long-range order by X-ray diffraction (XRD), while Fourier transform Raman (FT-Raman) spectroscopy was used to analyze the short-range order. To this end, the SBN orthorhombic phase was observed for all samples hear treated from 400 to 700 degrees C for 2 h. In addition, photoluminescence measurements were employed to study the structural modifications in SBN lattice. The characteristic red emission of the Eu3+ using the 488 nm exciting wavelength of an argon-ion laser was distinctly observed for SBN:Eu samples heat treated from 550 to 700 degrees C. Europium characteristic emission bands are related to D-5(l)-> F-7(J) (J = 0-2) transitions at 538 and 555 nm, as well as the D-5(0)-> F-7(J) (J = 0-4) ones at 580, 592, 615, 653 and 695 nm. By means of the emission spectra analyses it was possible to predict that the Eu3+ ions are located at sites of higher symmetry, since the relative area of the (D-5(0)-> F-7(2))/(D-5(0)-> F-7(1)) transitions for the SBN:Eu samples decrease from 3.82 to 2.60 with increasing temperature from 550 to 700 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Photoluminescence; Strontium bismuth niobate; Europium; Polymeric precursor method